Evaluation of Argulus indicus on striped snakehead (Channa striata) in Towuti Lake, South Sulawesi, Indonesia (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Amriana, Sari KD, Sriwulan, Anshary H. 2022. Evaluation of Argulus indicus on striped snakehead (Channa striata) in Towuti Lake, South Sulawesi, Indonesia. Biodiversitas 23: 1355-1362. Fish parasites are frequently present in wild freshwater fish populations, but data are limited on their distribution and impacts. This research aimed to investigate the severity of parasitic Argulus infestation on striped snakeheads (Channa striata) caught in Towuti Lake based on prevalence, intensity, and the bacteria associated with Argulus parasitizing C. striata. The research was conducted from March 2018 to February 2019 at Towuti Lake, South Sulawesi Province, Indonesia. Striped snakehead samples were captured using fish traps and gillnets. Samples of bacteria associated with Argulus were collected from four striped snakeheads (three infested and one non-infested control). Bacteria from Argulus attachment sites were identified through Vitek-2 Compact biochemical tests. Argulus prevalence on striped snakeheads was in the range 73.3-96.7%, with a mean intensity range of 2.18-14.43 and mean abundance 1.67-13.47. Water quality parameters measured in Towuti Lake remained within the Indonesian standards for freshwater fish habitat. The bacteria in striped snakehead mucus comprised two species in control (Staphylococcus xylosus, Pantoea sp.) and seven species in the parasitized fish (Micrococcus luteus, Bacillus mycoides, Acinetobacter baumannii, Sphingomonas paucimobilis, Pantoea sp., Aerococcus viridans, Staphylococcus arlettae). This study found a very high prevalence of striped snakehead infestation with parasitic A. indicus at low to medium intensity levels. The study also showed that A. indicus infestation was accompanied by and likely stimulated pathogenic bacteria, which can cause skin infections in fish. Therefore, A. indicus could be considered a threat to striped snakehead populations in Towuti Lake.
Keywords: Fish lice, infection, parasite, pathogen, wild fish